INCREASING OIL RECOVERY THROUGH LOW-TENSION POLYMER FLOODING - Sugihardjo Sugihardjo (Scientific Contributions Oil and Gas, 1999)
After completing a waterflood activity, the need of enhancing oil recovery (EOR) is essential. The selection of appropriate EOR methods that will be applied to particular field, as an effort to increase oil recovery, mainly depens on the reservoir characteristics and fluid behaviors.